Softwareland Chronicles: A Software Development Meta-Process Proposal - Bolaños Castro, Sandro Javier; González-Crespo, Rubén; Pascual-Espada, Jordán; García-Díaz, Vicente; Osis, Janis (Applied Computer Systems, 2017)
This paper presents the software development meta-process (SD-MP) as a proposal to set up software projects. Within this proposal we offer conceptual elements that help solve the war of methodologies and processes in favor of an integrating viewpoint, where the main flaws associated with conventional and agile approaches are removed. Our newly developed software platform to support the meta-process is also presented together with three case studies involving projects currently in progress, where the framework proposed in SD-MP has been applied.
Keywords: software process and methodology modeling language; software development meta process; Emerging